Karakterisasi dan Uji Efektivitas Sediaan Gel Aloe vera Kombinasi Kitosan sebagai Antibakteri Staphylococcus aureus - Sari Edi Cahyaningrum; Perintis Gita Susanti (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2022)
The study about development synthesis gel of Aloe vera combination chitosan as Staphylococcus aureus antibacterial has been done. This study has the aim to determine the effect of composition comparison of Aloe vera with chitosan on the characterization and effectiveness of Staphylococcus aureus antibacterial as a candidate for wound healing. The synthesis the gel of Aloe vera combination chitosan was made by mixing of Aloe vera and chitosan solution with weight variated 2:1; 1:1; and 1:2 (AvK1, AvK2, and AvK3), and addition of Na-CMC, glycerin, and propylene glycol, which the gel was neutralized until it reached pH 6,5–7,0. The gel preparation were characterized by organoleptic, measuring viscosity, functional groups identification, and effectiveness test of Staphylococcus aureus antibacterial by diffusion method. The results were shown based organoleptic observations by color, smell, and texture. The lowest viscosity measurement characterization was showed by AvK3 gel, which was 13.0412 mPa.s. The result functional groups identification of all gel preparations was indicated the presence of O–H and N–H stretching vibrations, C=O stretching vibrations, C–H bending vibrations, and C–O stretching vibrations. Staphylococcus aureus antibacterial test from gel of Aloe vera combination chitosan with various variations were shown effective result, which the strongest was shown by AvK1 gel with an inhibition zone of 26 mm. Key words: chitosan, Aloe vera, antibacterial, Staphylococcus aureus